The Phenomenon of Urban Culture in Film Dendang Bantilang - Damar Tri Afrianto (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2019)
Film titled Dendang Bantilang Director M. Ikhwan is one of the films that focus on cultural issues primarily in Bulukumba Regency. As a work of film, in addition to serving an aesthetic spectacle, but also showing the reality of the existence of a legend that is in the middle of a Pinisi of the current global era. This film does not only show the existence of pinisi at present, but show how urban culture contestation takes place in Bulukumba contextually. This is why the concern of this research leads to aspects of urban culture in the phenomenon in the film Dendang Bantilang. Through the method of semiotics Roland Barthes, this research found several realities behind their urban phenomenon in Bulukumba, among them: 1) the ceased of the chain of inheritance skills in the community of Bulukumba in making the pinisi ship as the main livelihood, 2) The fascination of work outside the village especially in Malaysia, and 3) The work of making Pinisi ship with a long process has an impact on the cost of wages that received late because wait for the completion of the shipbuilding. The results of the research showing the film Dendang Bantilang can be a reflection of contemplation that maintaining and harmonizing pinisi culture requires a strong and high awareness effort. Pinisi is the ancestral heritage of Indonesian culture both in form and knowledge, not to improve the flow of urban culture accompanied by the extinction of knowledge and skills about Pinisi.